Pengaruh Model Cooperative Script Terhadap Aktivitas Belajar Tema Kayanya Negeriku pada Siswa Kelas IV SDN 101729 Kampung Lalang - Farida, Arany; Harahap, Syarifah Ainun; Ramadhan, Nuri (Medan Resource Center, 2024)
This study employed a True-Experimental Design involving all fourth-grade students at SDN 101729 Kampung Lalang, with a total of 56 participants, divided into an experimental group and a control group, each consisting of 29 students. The data collection method used was a performance test, which was validated through a rater reliability test and content validation. The hypothesis was tested using the independent sample t-test. The research findings indicate that the pretest data from both the experimental and control groups were normally distributed and homogeneous. The t-value for the pretest was smaller than the t-table (0.036 < 0.05), indicating that there was no significant difference between the two groups before the intervention. However, the posttest results showed that the t-calculated value (0.729 > 0.05) was higher than the t-table, indicating a significant effect of the Cooperative Script Model on students' learning interest. The findings suggest that the Cooperative Script Model is more effective in enhancing learning interest compared to conventional methods. This model is recommended for further implementation in other subjects to increase student engagement.